Cultural Diversity in the Use of Action Verbs in Indonesian Senior High School English e-Textbooks: A Qualitative Content Analysis - Jennifer, Jennifer; Ena, Ouda Teda (Universitas Negeri Semarang, 2020)
Having a purpose of providing all Indonesian students with cheap but qualified textbooks, the e-textbooks should be culturally inclusive, which are able to make the students engage with the texts, and later be motivated to learn. Ena (2013) and Wulandari (2019) found cultural biases in English e-textbooks for senior high schools in Indonesia, which could demotivate students from certain cultural groups, which were underrepresented or represented unfairly. Thus, aiming to elaborate to what extent diversity is represented in the action verbs of the e-textbooks studied, qualitative content analysis was chosen for this study. The reseachers were the main instruments, followed by categorizations and interraters. The results showed there was ethnicity bias. There was no Melanesian animal subjects using action verbs at all in all the e-textbooks and Melanesian human subjects never dominated any e-textbook, while Foreign subjects, who in reality are less in number than the Melanesian, dominated the e-textbook for grade X. Since there was ethnicity bias in the e-textbooks, all the parties involved in the creation of the e-textbooks should either vary the writer team’s ethnicities or vary the texts’ cultural settings and make them in line with the population rank of ethnicities in Indonesia.